Improving Junior High Students' English Vocabulary with Cake App: Meningkatkan Penguasaan Kosakata Bahasa Inggris Siswa melalui Aplikasi Cake - Hatuina, Novi Dwi Putri; Astutik, Yuli (Indonesian Journal of Education Methods Development, 2024)
General Background: The rapid advancement of technology and globalization necessitates innovative educational tools, particularly in language learning. Specific Background: English vocabulary acquisition is critical for effective communication in a global context, yet there is limited research on the use of mobile-assisted language learning (MALL) applications in this area. Knowledge Gap: While various MALL applications are available, their specific impacts on vocabulary mastery among junior high students remain underexplored. Aims: This study investigates the effectiveness of the Cake application in improving vocabulary mastery among eighth-grade students at SMP Muhammadiyah 5 Sidoarjo, comparing it to traditional teaching methods. Results: Utilizing a true-experimental design with pre-test and post-test assessments for both control and experimental groups, the analysis conducted via SPSS 26 revealed a significant improvement in the experimental group’s vocabulary mastery. Novelty: This research highlights the Cake application as a viable instructional tool, showcasing its potential to engage students and enhance learning outcomes. Implications: The findings emphasize the transformative role of educational technology in facilitating English vocabulary development, providing valuable insights for educators seeking to integrate innovative methods into their language teaching practices. Highlights: Innovative Tool: The Cake application effectively supports vocabulary mastery in junior high students. Experimental Design: A true-experimental approach demonstrated significant improvements in learning outcomes. Technology Integration: The study highlights the potential of mobile apps to enhance student engagement in language learning. Keywords: Cake application, vocabulary mastery, junior high students, mobile learning, educational technology